Contrasting mechanisms displayed by stomatal conductance and CO2 fixation in responde to water deficit and recovery in cashew plants - Sousa, Raysa Mayara de Jesus (2024)
Due to climate change, adverse events such as the incidence of water deficit, particularly in vulnerable regions such as in Brazilian semi-arid regions, are expected to increase and become more frequently, leading to decrease agricultural yield and food security. The cashew tree (Anacardium occidentale L.) is a perennial, evergreen plant widely cultivated in northeastern Brazil, as well as in continents such as Africa, Asia, Central America, and Oceania. Cashew production is primarily concentrated in intertropical regions, which are typically characterized by low soil fertility and irregular rainfall throughout the year. In this context, this study objective was to investigate the mechanisms related to stomatal conductance and photosynthetic regulation in cashew plants exposed to water deficit. To this, the thesis was initially divided into two chapters. In the chapter I, it is presented a review of how cashew plants tolerate extreme environmental conditions, such as drought in semi-arid regions, emphasizing their evergreen characteristics. I the chapter II, it is presented the manuscript in preparation’ results, detailing the temporal mechanisms of stomatal conductance and CO2 assimilation in response to water deficiency and subsequent rehydration in cashew plants. The results from this study showed that, although cashew plants did not exhibit significant morphophysiological changes, photosynthesis (A) and stomatal conductances (gs) were severely affected. During the light curve kinetics, rehydrated plants (5 days post-stress) did not fully recover the A and gs levels observed under control conditions. However, these parameters, assessed during the transition of light and CO2 kinetics, exhibited distinct responses, indicating that cashew plants can enhance A and gs gs performance to levels comparable to or even exceeding those of control conditions upon recovery. Additionally, cashew plants demonstrated a low sensitivity to CO2, particularly in the recovered group, resulting in reduced water-use efficiency. Overall, our findings suggest that cashew plants possess distinct mechanisms for coping with abiotic stress, including stomatal regulatory responses.